Effect of harvest date on barley grain contamination with Fusarium spp. and deoxynivalenol in northeastern Ontario - Xue, Allen; Rowsell, John; Ho, Keh; Chen, Yuanhong; Chi, Dawn; Manceur, Ameur; Zhang, Shuzhen; Ren, Changzhong (Phytoprotection, 2013)
The effect of harvest date on the incidence of seed-borne Fusarium spp. and deoxynivalenol (DON) concentration in barley (Hordeum vulgare L.) was studied using three cultivars at three locations in Ontario in both 2004 and 2005. The profile of seed-borne Fusarium spp. was dominated by F. equiseti (Corda) Sacc., F. sporotrichioides Sherb., and F. poae (Peck) Wollenw., isolated from 4.4%, 3.3%, and 1.6% of the kernels, representing 39.3%, 29.4%, and 14.2% of the Fusarium pathogen population, respectively. Fusarium graminearum Schwabe and F. avenaceum (Fr.) Sacc. were each recovered from <1% of the kernels and represented 8.3% and 6.6% of the pathogen population, respectively. Other species, including F. acuminatum Ellis & Everh., F. culmorum (W.G. Sm.) Sacc., and F. semitectum Berk. & Rav., collectively occurred only on 0.2% of all kernels and represented <2% of the population. The incidence level of all Fusarium spp. increased from 6.9 to 13.9% when harvest was delayed. Of the commonly recovered species, only F. avenaceum and F. sporotrichioides levels increased with the delayed harvest, while other species did not follow a clear pattern. DON concentration in the harvested grain ranged from 0.20 to 0.28 mg kg‑1 with the five harvest dates, and was not statistically different. Significant differences in the incidence of all Fusarium spp. and in DON concentration were observed among cultivars, locations, and between the 2 yr of the study. The highest DON concentration observed in this study was 0.5 mg kg‑1, which is below the Canadian tolerance level of 1.0 mg kg‑1.